2007
DOI: 10.1111/j.1526-4610.2006.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topiramate for the Treatment of Chronic Migraine: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Objective.-To evaluate the efficacy and safety of topiramate (100 mg/day) compared with placebo for the treatment of chronic migraine.Methods.-This was a randomized, placebo-controlled, parallel-group, multicenter study consisting of 16 weeks of double-blind treatment. Subjects aged 18 to 65 years with 15 or more headache days per month, at least half

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
390
3
21

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(428 citation statements)
references
References 24 publications
14
390
3
21
Order By: Relevance
“…If proven effective, it would be the first migraine prophylactic agent developed on the basis of the CSD hypothesis (Goadsby et al 2009b). Other examples of potential compounds effective as preventive therapy for chronic migraine are Memantine, an activity-dependent N-methylD-aspartate receptor blocker, and Topiramate (Diener et al 2007, Silberstein et al 2007, Bussone et al 2005, Storer and Goadsby 2004, both inhibiting CSD (Goadsby et al 2009b, Akerman andGoadsby 2004). In an attempt to correlate the preventive action of a range of medications with an effect on CSD, Ayata et al (2006) have studied topiramate, valproate, amitriptyline, propranolol and methysergide.…”
Section: Discussionmentioning
confidence: 99%
“…If proven effective, it would be the first migraine prophylactic agent developed on the basis of the CSD hypothesis (Goadsby et al 2009b). Other examples of potential compounds effective as preventive therapy for chronic migraine are Memantine, an activity-dependent N-methylD-aspartate receptor blocker, and Topiramate (Diener et al 2007, Silberstein et al 2007, Bussone et al 2005, Storer and Goadsby 2004, both inhibiting CSD (Goadsby et al 2009b, Akerman andGoadsby 2004). In an attempt to correlate the preventive action of a range of medications with an effect on CSD, Ayata et al (2006) have studied topiramate, valproate, amitriptyline, propranolol and methysergide.…”
Section: Discussionmentioning
confidence: 99%
“…The encouraging results from a small randomized, placebo-controlled trial (RCT) of topiramate (50 mg daily) in 28 patients with CM and medication overuse paved the way for larger studies [58]. Two multicentre, parallel-group RCT in Europe (59 patients) and the USA (328 patients) showed that topiramate at a daily dose of 100 mg during 16 weeks was effective as a preventive therapy for CM [59,60]. The effect size was overall modest, however, with a mean reduction in monthly migraine days of 3.5 (versus placebo -0.2) and a numberneeded-to-treat of 12.5 [61].…”
Section: Topiramatementioning
confidence: 99%
“…FTTF esetén alkalmazandó, specifi kus preventív kezelésről szóló tanulmányok csak elvétve áll-nak rendelkezésre, ezért a preventív szer kiválasztásánál a primer fejfájás típusa (migrén vagy tenziós típusú), a szer mellékhatásai, a társbetegségek (amelyek között nagy gyakoriságuk miatt kiemelt fi gyelmet érdemelnek a hangulatzavarok és más pszichés kórképek), illetve a beteg igényei és a megelőző terápiás tapasztalatok a mérv-adóak. A topiramát hatékonyságát nyílt vizsgálatok után placebokontrollált vizsgálatok is igazolták krónikus migrénhez társuló gyógyszer-túlfogyasztás esetén [57,58]. Több nyílt klinikai vizsgálat igazolta a valproát, illetve [59].…”
Section: Profi Laktikus Terápiaunclassified